Stiffening of graphene oxide films by soft porous sheets - Lily Mao (Nature Portfolio, 2019)
Graphene oxide sheets have been used as a model system to study how the mechanical properties of individual 2D building blocks scale to their bulk form. Here the authors show that the modulus of multilayer graphene oxide films can be enhanced if some of the sheets are weakened by introducing in-plane porosity.